Mitos dalam Tegangan antara Figur Lelaki Ideal dan Realistis dalam Iklan Head & Shoulders “Joe Taslim x Fadil Jaidi” - Oktavia, Salsabilla Putri; Ramdani, Guruh (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
Visual elements play a strategic role in shaping consumer perceptions of advertisements, particularly within the context of contemporary digital communication. This study analyzes the representation of male figures in the Head & Shoulders advertisement titled "Joe Taslim X Fadil Jaidi: Who Will Be the Next Brand Ambassador of Head & Shoulders?" published on May 27, 2022. The advertisement draws attention by featuring two public figures with contrasting characteristics: Joe Taslim, who embodies conventional masculinity, and Fadil Jaidi, who is portrayed as relaxed and humorous. Utilizing Roland Barthes’ semiotic approach, this research aims to examine how the myth of the ideal male figure is constructed, and how the tension between idealized and more casual representations of masculinity generates specific ideological meanings within the advertisement. The findings reveal that the advertisement constructs a myth of inclusive modern masculinity through the negotiation between ideal and realistic male portrayals. This study indicates that the advertisement functions not merely as a promotional tool, but also as a vehicle for disseminating the ideology that self-confidence and an ideal appearance are attainable for all men through personal grooming. Such representational strategies expand market reach, challenge traditional masculinity stereotypes, and leverage digital media as a platform for cultural influence.